2015
DOI: 10.1002/jcsm.12074
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐sarcopenic effects of diamino‐diphenyl sulfone observed in elderly female leprosy survivors: a cross‐sectional study

Abstract: BackgroundIt has been reported that 4,4′‐diamino‐diphenyl sulfone (DDS), the longtime treatment of choice for leprosy, prolongs the lifespan and increases mobility in animal models by reducing the levels of reactive oxygen species and inhibiting muscle pyruvate kinase activity. This study aimed to investigate whether sarcopenic status in leprosy survivors was influenced by recent history of DDS medication.MethodsForty‐one elderly female leprosy survivors were recruited. The DDS group was defined as survivors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The results from a randomized controlled trial of angiotensin-converting enzyme (ACE) inhibitors on physical function involving 130 older patients with impairment of daily activities suggest a beneficial effect of ACE inhibitors in sarcopenia [91] . In a recent study, leprosy survivors who had taken 4,4′-diamino-diphenyl sulfone showed greater skeletal muscle mass and strength than those who had not taken the drug [92] . This result suggests that drug repurposing is a new strategy for the therapeutic approach of sarcopenia.…”
Section: Possible Therapeutic Intervention Strategiesmentioning
confidence: 94%
“…The results from a randomized controlled trial of angiotensin-converting enzyme (ACE) inhibitors on physical function involving 130 older patients with impairment of daily activities suggest a beneficial effect of ACE inhibitors in sarcopenia [91] . In a recent study, leprosy survivors who had taken 4,4′-diamino-diphenyl sulfone showed greater skeletal muscle mass and strength than those who had not taken the drug [92] . This result suggests that drug repurposing is a new strategy for the therapeutic approach of sarcopenia.…”
Section: Possible Therapeutic Intervention Strategiesmentioning
confidence: 94%
“…[57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns. [57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, 64-71 as well as the emergence of reports on patient groups, commentaries, and political campaigns.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…Detailed pathophysiology was the subject of many reports into what happens in specific cachexia syndromes [50][51][52][53][54][55][56] and in other non-cancer-related cachexia and sarcopenia syndromes. [57][58][59][60][61][62][63] As befits a series of fields that are relatively new and not the main speciality of many practitioners, there was a large number of informative review articles, [64][65][66][67][68][69][70][71] as well as the emergence of reports on patient groups, commentaries, and political campaigns. 72…”
Section: By Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cachexia is a complex syndrome, characterized by weight loss consisting of skeletal muscle loss and adipose tissue wasting, leading to poor outcomes . There are no established treatments for cancer cachexia, although recent pre‐clinical and clinical studies have shown the promising effects of several agents including ghrelin, myostatin/activin pathway antagonists, androgenic steroids and selective androgen receptor modulators, megestrol acetate, trimetazidine, espindolol, and diamino‐diphenyl sulfone on muscle wasting.…”
mentioning
confidence: 99%